Identifikasi Urutan Prioritas Penanganan dalam Pemeriksaan Kondisi Jembatan dengan Metode Bridge Management System (BMS) - Akbar, Abi Oktariva; Handayani, Elvira; Dwiretnani, Annisaa; Zulfiati, Ria (Jurnal Talenta Sipil, 2024)
One piece of infrastructure that has an important role in a road network is a bridge. Bridges are land transportation infrastructure that is useful for continuing roads through existing obstacles such as rivers, so the collapse of a bridge will reduce or hold up traffic, which means disrupting the smooth transportation of people and goods. A bridge is a structure that crosses a river or other traffic barrier, so the collapse of the bridge will reduce or hold back traffic, which as a result will disrupt the comfort of traffic and disrupt economic relations. The purpose of a bridge inspection is to ensure that the bridge is in a safe condition for road users and also to secure the investment value of the bridge. In this thesis, we will discuss the identification of bridge condition checks which are carried out directly by conducting field surveys.